Real Feelings : Emotion and Technology - Himmelsbach, Sabine; Koek, Ariane; Spaninks, Angelique (S.l. : Christoph Merian Verlag, 2020)
Catala, Antoine ; Deja, Stine ; Munk, Marie ; Dewey-Hagborg, Heather ; Emard, Justine ; Evans, Cécile B. ; Fornieles, Ed ; Guta, Maria ; Ganea, Adrian ; Hunziker, Esther ; Lambelet, Clément ; Lorem ; McCarthy, Lauren Lee ; McDonald, Kyle ; McRae, Lucy ; Niquille, Simone C. ; Ploeger, Dani ; Kim, Seokyung ; Kimyonghun, Shinseungback ; Tammi, Maija ; Troika ; Vogelaar, Coralie ; Young, Liam
Real Feelings. Emotion and Technology, HeK (House of Electronic Arts Basel), Basel, August 27 - November 15, 2020 ; MU Hybrid Art House, Eindhoven, March 26 - June 6, 2021
boek